Nós somos Anonymous: as relações comunicacionais entre o Coletivo Anonymous e a mídia - Antonio, Bruno Luiz Cardoso Tavares (2013)
This study aims to examine how communicational relationships are established between Anonymous collective and the mass media such as television, radio and print media. Anonymous began as a small group of internet users seeking fun in the imageboard 4chan. Later on, the group gained a more serious stance, chasing free exchange information, freedom of speech and free Internet usage. It has become a media phenomenon that resulted in a collective of cyberactivists with unclear political objectives and became popular after being recognized for: shutting down government websites, confidential information leakage and stolen data. The goal of this research is to (i) demonstrate how media builded and explored an image of a collective that is mobilized through social networks to organize concomitant protests in several parts of the world and (ii) explain how media uses Anonymous for their own ends and, in the Brazilian case, how it has appropriated Guy Fawkes mask as a symbol against corruption